Time Complexity Analysis of Cloud Data Security: Elliptical Curve and Polynomial Cryptography - Pharkkavi, D; Maruthanayagam, D (International Journal of Computer Sciences and Engineering, 2019)
Encryption becomes a solution and different encryption techniques which roles a significant part of data security on cloud. Encryption algorithms is to ensure the security of data in cloud computing. Because of a few limitations of pre-existing algorithms, it requires for implementing more efficient techniques for public key cryptosystems. ECC (Elliptic Curve Cryptography) depends upon elliptic curves defined over a finite field. ECC has several features which distinguish it from other cryptosystems, one of that it is relatively generated a new cryptosystem. Several developments in performance have been found out during the last few years for Galois Field operations both in Normal Basis and in Polynomial Basis. On the other hand, there is still some confusion to the relative performance of these new algorithms and very little examples of practical implementations of these new algorithms. Efficient implementations of the basic arithmetic operations in finite fields GF(2m) are need for the applications of coding theory and cryptography. The elements in GF(2m) know how to be characterized in a choice of bases. A variety of basis used to represent field elements has a major impact on the performance of the field arithmetic. The multiplication techniques that make use of polynomial basis representations are very efficient in comparison to the best techniques for multiplication using the other basis representations. In this paper, focuses on user confidentiality and security protection in cloud, and that uses enhanced ECC technique over Galois Field GF(2m). The strong point of the proposed ECPC (Elliptical Curve and Polynomial Cryptography) algorithm is based on the complexity of computing discrete logarithm in a large prime modulus, and the Galois Field allows mathematical operations to mix up data effectively and easily. This technique is mainly used to encrypting and decrypting data to ensure security protection and user confidentiality in the cloud computing. Results show that the performance of ECPC over Galois Field, in two region of evaluation, it has better than the other technique that is used for comparison purpose.